2014
DOI: 10.11648/j.avs.20140202.15
|View full text |Cite
|
Sign up to set email alerts
|

Social and Quality Attributes Influencing Consumption of Native Poultry in Eastern Uganda

Abstract: Poultry consumers in Uganda are increasingly interested in consumption of native chicken compared to duck and turkey meat. By far the most important driving force for selective consumption is preference. The aim of this study was to determine the factors that influence preference for consumption of native poultry in Butaleja and Tororo districts. A field survey of rural and peri-urban poultry consumers and food service providers was conducted through semi-structured interviews using questionnaires; and a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In contrast, there was no statistically signi cant association (χ 2 = 0.04; p = 0.846) between respondents' propensity to consume native chicken meat and their marital status. This suggests that native chicken meat consumption patterns were not greatly in uenced by marital status (Higenyi 2014). Similarly, the analysis indicated no statistically signi cant association (χ 2 = 1.36; p = 0.243) between consumer consumption of native chicken meat and habitat (rural or urban).…”
Section: Results and Discussion A) Preferences For Native Chicken Meatmentioning
confidence: 96%
“…In contrast, there was no statistically signi cant association (χ 2 = 0.04; p = 0.846) between respondents' propensity to consume native chicken meat and their marital status. This suggests that native chicken meat consumption patterns were not greatly in uenced by marital status (Higenyi 2014). Similarly, the analysis indicated no statistically signi cant association (χ 2 = 1.36; p = 0.243) between consumer consumption of native chicken meat and habitat (rural or urban).…”
Section: Results and Discussion A) Preferences For Native Chicken Meatmentioning
confidence: 96%
“…During the interview and farmer group discussions (FGD), the major disease easily recognized by thevillagers was Ranikhet disease, fowl pox and parasitic infestation (Chaka, et al, 2012;Billah et al, 2013;Mulisa et al, 2014). Most of the time of the year, desirable characters namely, hardiness, adaptability to the wide agroclimatic variability ranging from tropical to subtropical climate, disease tolerance, and flavour of meat and eggs of native chicken germplasm protects them from several infection (Higenyi, et al, 2014;Terefe et al, 2015;Singh et al, 2017).…”
Section: Diseases and Health Managementmentioning
confidence: 99%
“…Theieme, et al, (2014) [15] reported that, it serve as source of nutrients of high biological (protein) value through eggs and meat, sonaiya and Swam (2004) [14] inferred that keeping poultry makes a substantial contribution to household food security throughout the developing world: It helps diversify income and provides quality food, energy, fertilizer and a renewable asset in over 80 percent of rural households. Also, the work of Higenyi, et al (2014) [9] disclosed that native poultry meat is a cheap source of protein and household income particularly to the poor rural and peri-urban families in developing countries. Consequent on the above advantages, this study thus, evaluates the characteristics of extensive poultry farmers in Niger State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%